Analisis Sistem Proses Pindah Massa pada Ekstraksi Secara Mekanik Minyak Kedelai (Glycine Max Oil) - Bambang Dwi Argo (PERTETA, 2010)
Abstract Soybean, a vegetable protein-rich commodity needed to improve public nutrition, safe to consume, and the price affordable. The purpose of this research are to: 1. determine the effect of pressure and time of extraction the mass balance, yield and level of soybean oil extraction, 2. Gain mass transfer coefficient value in soybean oil extraction process, and 3. analyze the mechanism of mass changes during the extraction process soybean oil is mechanically using hydraulic pressing. Oil obtained results indicate an increase due to the influence of a given amount of pressure and length of time silenced. The greater the pressure exerted, the more oil produced this shows soybean oil can come out with a maximum at the greatest pressure of 200 kg/cm2. Mass transfer coefficient in soybean oil extraction process at a pressure of 100 kg/cm2 5.57x10-5 gcm3/cm seconds. In the pressure is 200 kg/cm2 15.39 x 10-5g cm3/cm seconds. Keywords: mass transfer, mechanical extraction, soybean oil Diterima: 12 Maret 2010; Disetujui: 7 September 2010